Bacterial colonization and antimicrobial resistance genes in neonatal enteral feeding tubes. Issue 4 (27th March 2019) - Taft, Diana H; Salinero, Lauren K; Vongbhavit, Kannikar; Kalanetra, Karen M; Masarweh, Chad; Yu, Alice; Underwood, Mark A; Mills, David A
ABSTRACT: Enteral feeding is a key component of care in neonatal intensive care units (NICUs); however, feeding tubes harbor microbes. These microbes have the potential to cause disease, yet their source remains controversial and clinical recommendations to reduce feeding tube colonization are lacking. This study aims to improve our understanding of the bacteria in neonatal feeding tubes and to evaluate factors that may affect these bacteria. 16S rRNA gene sequencing was used to characterize the bacteria present in pharyngeal, esophageal, and gastric portions of feeding tubes, residual fluid of the tubes, and infant stool using samples from 47 infants. Similar distributions of taxa were observed in all samples, although beta diversity differed by sample type. Feeding tube samples had lower alpha diversity than stool samples, and alpha diversity increased with gestational age, day of life, and tube dwell time. In a subset of samples from 6 infants analyzed by whole metagenome sequencing, there was greater overlap in transferable antimicrobial resistance genes between tube and fecal samples in breast milk fed infants than in formula fed infants. These findings develop our understanding of neonatal feeding tube colonization, laying a foundation for research into methods for minimizing NICU patients' exposure to antimicrobial resistant microbes. Abstract : The bacteria and antimicrobial resistance genes found in neonatal feeding tubes overlap with those found in infant stool.